(untitled) (Bangladesh Medical Journal, 2016)
This study was carried out to evaluate the pattern of contraceptive usage in family planning clinics of public hospitals within Ilorin metropolis, Nigeria. It was a retrospective study carried out between January 2010 and December 2012 involving a total of 10,002 contraceptive users attended family planning clinics in the centers within this period. Over a half of the clients (56.6%) were within the age bracket of 30-39 years, and 1.4% were less than 20 years. Majority (79.8%) of the users had two or more children while 0.9% were nulliparas. The most preferred contraceptive method was the hormonal injectable (59.5%); the percentage of users of oral contraceptive pills was 9.6% and utilization of the male condoms was 6.9%. The user rate for intrauterine contraceptive device was 17.3% while it was 6.6% for hormonal implant. Surgical sterilization was utilized by 0.1%. The commonest source of information was from healthcare personnel accounting for 41.9% followed by the mass media (21.6%). There was a low level of acceptance amongst teenagers; the level of acceptance of surgical sterilization methods was also low. There is need to improve on information dissemination regarding contraceptive use, via the internet and social media for teenagers who tend to be more internet-savvy. The number and age of clients were statistically significant factors for patterns of contraceptive usage at various family planning clinics in Ilorin metropolis. Bangladesh Med J. 2015 Sep; 44 (3): 140-145